2020
DOI: 10.1186/s12984-020-00687-1
|View full text |Cite
|
Sign up to set email alerts
|

Online compensation detecting for real-time reduction of compensatory motions during reaching: a pilot study with stroke survivors

Abstract: Background Compensations are commonly observed in patients with stroke when they engage in reaching without supervision; these behaviors may be detrimental to long-term functional improvement. Automatic detection and reduction of compensation cab help patients perform tasks correctly and promote better upper extremity recovery. Objective Our first objective is to verify the feasibility of detecting compensation online using machine learning methods and pressure distribution data. Second objective was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Similarly, in the reviewed studies, marker-based motion capture systems were proven to be able to effectively identify compensation. In all, 5 studies have been used as the ground truth for the measurement of the effectiveness of other sensors in compensation detection [ 42 , 43 , 45 , 86 , 87 ]. Several interesting findings were reported using marker-based motion capture systems: (1) pre- and posttests showed that both robotic [ 32 , 38 , 63 ] and MR therapies [ 26 ] elicited benefits on reducing trunk compensatory movements, and stroke survivors showed less trunk compensatory movements during VR reaching [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in the reviewed studies, marker-based motion capture systems were proven to be able to effectively identify compensation. In all, 5 studies have been used as the ground truth for the measurement of the effectiveness of other sensors in compensation detection [ 42 , 43 , 45 , 86 , 87 ]. Several interesting findings were reported using marker-based motion capture systems: (1) pre- and posttests showed that both robotic [ 32 , 38 , 63 ] and MR therapies [ 26 ] elicited benefits on reducing trunk compensatory movements, and stroke survivors showed less trunk compensatory movements during VR reaching [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Barriers to health care access intensified during the pandemic and XR telehealth emerged as a responsive option. XR telehealth had a particularly significant impact to increase the immediacy of care and access among medically and geographically isolated populations who required continual rehabilitation services [ 62 , 63 ]. In addition to providing immersive and accessible care, XR telehealth connected people in virtual spaces to combat social isolation and maintain health-promoting social relationships over distances [ 64 ].…”
Section: Xr For Telehealth During Covid-19mentioning
confidence: 99%
“…Recent studies start addressing the compensation in the design of VR-based rehabilitation through applying various motion tracking technology [16,17, 18] as well as the pressure sensors [19,20] to detect compensatory movements when stroke survivors perform the UE reaching tasks. For example, Foreman and Engsberg [17] utilized one commercial Kinect device in their VRShape system to measure and shape the trunk compensatory movement during repetitive upper limb practices of a reaching task.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cirstea and Levin [10] found a signi cant correlation between the increased trunk involvement with a reduction in active ranges of elbow extension and shoulder exion when stroke individuals were asked to perform the reaching task. The monitoring of stroke survivor's compensation during motor practice is especially important at the context of community where the close supervision of therapist is usually missed.Recent studies start addressing the compensation in the design of VR-based rehabilitation through applying various motion tracking technology [16,17, 18] as well as the pressure sensors [19,20] to detect compensatory movements when stroke survivors perform the UE reaching tasks. For example, Foreman and Engsberg [17] utilized one commercial Kinect device in their VRShape system to measure and shape the trunk compensatory movement during repetitive upper limb practices of a reaching task.…”
mentioning
confidence: 99%
See 1 more Smart Citation